Oxidoreductases on their way to industrial biotransformations - Martínez, Angel T.; Ruiz-Dueñas, Francisco J.; Camarero, Susana; Serrano, Ana; Linde, Dolores; Lund, Henrik; Vind, Jesper; Tovborg, Morten; Herold-Majumdar, Owik M.; Hofrichter, Martin; Liers, Christiane; Ullrich, René; et al. (Biotechnology advances, 2017)
Fungi produce heme-containing peroxidases and peroxygenases, flavin-containing oxidases and dehydrogenases, and different copper-containing oxidoreductases involved in the biodegradation of lignin and other recalcitrant compounds. Heme peroxidases comprise the classical ligninolytic peroxidases and the new dye-decolorizing peroxidases, while heme peroxygenases belong to a still largely unexplored superfamily of heme-thiolate proteins. Nevertheless, basidiomycete unspecific peroxygenases have the highest biotechnological interest due to their ability to catalyze a variety of regio- and stereo-selective monooxygenation reactions with H2O2 as the source of oxygen and final electron acceptor. Flavo-oxidases are involved in both lignin and cellulose decay generating H2O2 that activates peroxidases and generates hydroxyl radical. The group of copper oxidoreductases also includes other H2O2 generating enzymes - copper-radical oxidases - together with classical laccases that are the oxidoreductases with the largest number of reported applications to date. However, the recently described lytic polysaccharide monooxygenases have attracted the highest attention among copper oxidoreductases, since they are capable of oxidatively breaking down crystalline cellulose, the disintegration of which is still a major bottleneck in lignocellulose biorefineries, along with lignin degradation. Interestingly, some flavin-containing dehydrogenases also play a key role in cellulose breakdown by directly/indirectly “fueling” electrons for polysaccharide monooxygenase activation. Many of the above oxidoreductases have been engineered, combining rational and computational design with directed evolution, to attain the selectivity, catalytic efficiency and stability properties required for their industrial utilization. Indeed, using ad hoc software and current computational capabilities, it is now possible to predict substrate access to the active site in biophysical simulations, and electron transfer efficiency in biochemical simulations, reducing in orders of magnitude the time of experimental work in oxidoreductase screening and engineering. What has been set out above is illustrated by a series of remarkable oxyfunctionalization and oxidation reactions developed in the frame of an intersectorial and multidisciplinary European RTD project. The optimized reactions include enzymatic synthesis of 1-naphthol, 25-hydroxyvitamin D3, drug metabolites, furandicarboxylic acid, indigo and other dyes, and conductive polyaniline, terminal oxygenation of alkanes, biomass delignification and lignin oxidation, among others. These successful case stories demonstrate the unexploited potential of oxidoreductases in medium and large-scale biotransformations. •Recent advances on fungal oxidoreductases for a bio-based economy are reviewed.•These include computer-aided rational design and directed evolution of biocatalysts.•Classical oxidoreductases consist of peroxidases/oxidases involved in lignin decay.•Peroxygenases and polysaccharide monooxygenases were more recently discovered.•Reviewed transformations consider both oxyfunctionalization and oxidation reactions.